2022
DOI: 10.1002/jimd.12556
|View full text |Cite
|
Sign up to set email alerts
|

A multinational study of acute and long‐term outcomes of Type 1 galactosemia patients who carry the S135L (c.404C > T) variant of GALT

Abstract: Patients with galactosemia who carry the S135L (c.404C > T) variant of galactose-1-P uridylyltransferase (GALT), documented to encode low-level residual GALT activity, have been under-represented in most prior studies of outcomes in Type 1 galactosemia. What is known about the acute and longterm outcomes of these patients, therefore, is based on very limited data. Here, we present a study comparing acute and long-term outcomes of 12 patients homozygous for S135L, 25 patients compound heterozygous for S135L, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Katler et al reported that individuals who are homozygous or compound heterozygous for the p.Ser135Leu GALT variant exhibited initial presentations similar to classic galactosemia in the neonatal period. Their long-term complications were similar to classic galactosemia regarding cognitive and motor dysfunctions [ 42 ]. Welsink-Karssies et al reported tremors in two individuals with clinical variant galactosemia who were homozygous for the p.Ser135Leu GALT variant.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Katler et al reported that individuals who are homozygous or compound heterozygous for the p.Ser135Leu GALT variant exhibited initial presentations similar to classic galactosemia in the neonatal period. Their long-term complications were similar to classic galactosemia regarding cognitive and motor dysfunctions [ 42 ]. Welsink-Karssies et al reported tremors in two individuals with clinical variant galactosemia who were homozygous for the p.Ser135Leu GALT variant.…”
Section: Discussionmentioning
confidence: 98%
“…The clinical variant galactosemia is due to hypomorphic alleles in GALT resulting in a higher residual GALT activity (1–10% of normal) [ 1 ]. The p.Ser135Leu GALT variant is the most commonly reported hypomorphic GALT variant associated with the clinical variant galactosemia [ 1 , 42 ]. Katler et al reported that individuals who are homozygous or compound heterozygous for the p.Ser135Leu GALT variant exhibited initial presentations similar to classic galactosemia in the neonatal period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations